The genotoxic properties of leaf extracts from three common congolese medicinal plants, Cogniauxia podolaena Baill. (1839), Dissotis rotundifolia (Sm.) Triana (1872) and Emilia coccinea G. Don (1839) using the Ames test, the in vitro micronucleus test and the comet assay (International Journal of Agricultural Research, Innovation and Technology, 2026)
Cogniauxia podolaena, Dissotis rotundifolia, and Emilia coccinea are widely used in the Democratic Republic of Congo to treat various ailments, but also as contraceptives, laxatives, painkillers, and to combat malaria. Although commonly used in traditional medicine, no genotoxicity or mutagenicity data exist for these species. This study aims to assess their potential in vitro genotoxic and mutagenic effects. The plant material was collected in Kinshasa and authenticated by botanist Blaise Bikandu at the herbarium of the Faculty of Sciences of the University of Kinshasa. Methanol, ethyl acetate, and water extracts of these species were prepared and subjected to the AMES test, the comet assay, and the micronucleus test. Genotoxicity was assessed using ethyl methanesulfonate (EMS) and benzo (a) pyrene (BaP). Extracts from C. podolaena tested positive in the AMES test, particularly on the TA98 strain, suggesting frame-shift mutations. Methanol extracts from all three plants caused dose-dependent DNA damage in the comet assay, while limited genotoxicity was observed for the aqueous extract of C. podolaena. Co-genotoxic effects were observed with EMS and BaP. Methanol extracts from all species and aqueous/EtOAc extracts from C. podolaena induced chromosomal abnormalities in the micronucleus test. The results suggest that these traditional medicinal plants contain genotoxic agents, warranting further toxicological studies.Int. J. Agril. Res. Innov. Tech. 15(2): 127-137, Dec 2025